Intestinal alterations in people with rheumatoid arthritis (Research, Society and Development, 2022)
Objective: This study aimed to analyze the main intestinal changes in people with Rheumatoid Arthritis (RA) and aspects related to them, highlighting the influence of alimentary changes resulting from intestinal symptoms (IS). Methods: Quantitative data were collected regarding age group, RA time of diagnosis, evacuation profile, IS, the influence of food on symptoms and socioeconomic aspects through the implementation of an adapted validated questionnaire (Souza et al., 2016) in groups of virtual social networks. Crosses between these data were performed to better clarify the main factors involved in this correlation. The results were calculated using the Statistical Packages of the Social Sciences® program. Results: 91 people with RA participated, with a mean age of 46,9 years. 96,7% were female and 3,3% male. An emphatic occurrence of IS in RA patients was revealed. The main symptoms reported were abdominal pain, nausea, flatulence, constipation and diarrhea. There was a significant prevalence of abdominal pain when relating IS with age group. 97,8% said they used medicinal drugs to treat RA and 2,2% denied. As a result of the IS, in which “constipation” and “nausea” were statistically significant, 68% reported changes in alimentation. The results also showed independence between IS and the socioeconomic profile of the respondents. Conclusion: A high prevalence of intestinal alterations in RA patients and alimentary changes as a result of IS was verified.